Surface Sand And Gravel Mine Fires - Maria I. De Rosa (The National Institute for Occupational Safety and Health (NIOSH), 2004)
Table 28 and figure 10 show the number of fires and fire injuries for surface sand and gravel mines by state during 1990-2001. Table 28 also shows the injury risk rates, employees' working hours, and lost workdays. At surface sand and gravel mines, a total of 70 fires with 60 injuries occurred in 29 states during 1990-2001. Fifty-nine of the fires caused 60 injuries (none of the fires involved contractors). The yearly average was 5.8 fires and five injuries. The Ewhr value was 741 x 106 hr (Irr = 0.016), and the LWD value was 6,921. California had the most fires (nine fires and five injuries), followed by Michigan (six fires and six injuries) and Pennsylvania (five fires and five injuries). Of these states, Pennsylvania had the highest injury risk rate value (Irr = 0.052). Table 29, partly illustrated in figure 11, shows the number of fires, fire injuries, risk rates, employees' working hours, and lost workdays by time period. The number of fires and fire injuries show an increase during the second period followed by a decrease during the fourth period followed by a small increase during the fifth period and a sharp decrease during the last period. Employees' working hours increased during most of the periods. The Irr values follow patterns similar to those shown by the injury values.